Employment chances of immigrants and their children in Germany: Does sense of personal control matter? - Anna Thum-Thysen (IZA Journal of Migration, 2016)
Labour market integration is a social process suggesting that personality traits are relevant. This paper explores whether immigrants with a higher belief in their ability to control outcomes tend to be more likely to be employed. This trait is known in psychology as the locus of control (LOC). I employ a model framework that allows LOC to depend on a set of observable determining variables. Results indicate that sense of personal control is correlated with employment probability and that there is a risk that immigrants and their children tend to have a more externalized LOC. Mother's education is a key factor correlated with the sense of personal control.
Keywords: J15; J24; M59; Z13; 330; Personality; Labour market; Unemployment